Anti-inflammatory, Anxiolytic and Antioxidant Property of Lactuca sativa L and Formulation of Microspheres Loaded Sustained Release Anti-inflammatory Gel - Gyawali, Rajendra; Ghimire, Anupama; Khatiwada, Apeksha; Niraula, Prakshit; Sharma, Ushma; Thapa, Roshani (Journal of Nepal Chemical Society, 2020)
Anti-inflammatory and anxiolytic properties of Lactuca sativa L extract was evaluated by formalin induced mice paw edema test, and elevated plus maze animal model respectively. Solid microspheres containing dispersed extract were obtained by water-in-oil-in-water multiple emulsion system followed by solvent evaporation method. Optimization was carried out using MINITAB 16 and optimized microspheres were loaded into a gel base. Anti-oxidant activity of optimized microspheres loaded gel was evaluated using DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. The gel was also evaluated for its physical properties, drug release kinetics and anti-inflammatory activity using formalin induced mice-paw edema test where the anti-inflammatory potential was compared to marketed diclofenac gel (1.16% w/w). All doses of extract as well as microsphere loaded sustained release anti-inflammatory gel showed a dose and time dependent inhibition of edema (P<0.05), the extract also showed a dose dependent inhibition of level of anxiety (P<0.001). Potential anti-oxidant activity was seen with different concentration of crude extract and microsphere loaded gel. The anti-oxidant potential was compared using IC50 value which was 5.62 µg/mL, 6.34 µg/ml, 8.25 µg/mL for ascorbic acid, methanolic extract of L. sativa and microspheres loaded gel respectively.